Cardioprotective Effect of Mango and Kinnow Peel Extracts on Doxorubicin-induced Cardiotoxicity in Albino Rats: Cardioprotective Effect of Mango and Kinnow Peel Extracts on Doxorubicin - Safdar, Muhammad Naeem; Kausar, Tusneem; Nadeem, Muhammad; Jabbar, Saqib; Ahmed, Salman; Taj, Touqeer; Tufail, Fatima; Mehmood, Waqas (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Different dose levels of mango (Mangifera indica L.) and kinnow (Citrus reticulate L.) peel extracts were administered to rats for 60 days and myocardial infarction was induced by administering doxorubicin (DOX) injection 2.5 mg/kg body weight (BW) intraperitoneal in six equal doses on alternate days from 50th to 60th day. Cardiac biomarkers lactate dehydrogenase (LDH), aspartate transaminase (AST), creatine kinase-MB fraction (CKMB), creatine phosphokinase (CPK), lipid profile (triglycerides, cholesterol,high density lipoprotein (HDL)) and low density lipoprotein (LDL), renal function activities (blood urea nitrogen, creatinine, uric acid) in serum and antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) in heart tissues were estimated. Histopathological studies were carried out for cardiac tissues of the studied rat groups. Mango and kinnow peel polyphenolic extracts at medium dose (i.e., 150 mg/kg BW) and high dose (i.e., 300 mg/kg BW) exhibited significant protection against doxorubicin induced myocardial infarction. Maximum cardioprotective activity was exhibited by groups pre-treated with 300 mg/kg of peel extracts, especially mango peel extracts, which maintained the membrane integrity of myocardial tissues, lowered the DOX-induced hyperlipidemia, nephrotoxicity and significantly restored the activity of cardiac endogenous antioxidant enzymes. Histopathological studies of cardiac tissues verifield the cardioprotective activity of both peels extracts at medium and high dose levels. Thus, mango and kinnow peel extracts have cardioprotective potential at medium and high dose levels.